Effects of Urdu Infotainment Programs on Pakistani People: Entertainment, Cultural and Vulgarity Concerns - Safdar, Ghulam; Raza, Hussain; Javed, Muhammad Naeem (Jurnal The Messenger, 2022)
Introduction: Infotainment is the term to entertain the public as well as to inform. Infotainment programs include shows based on funny analysis; parodies and moral issue based comedy to keep amuse the spectators. This research study explored the ‘Effects of Urdu Infotainment Programs on Pakistani People.’ The basic purpose of this study was to know about the effects of Pakistani well known infotainment programs on society.Methods: Study was conducted under the light of ‘Uses and Gratification Theory’ perspectives and method of survey was adopted and well-structured self-designed questionnaire used for data collection. Population of study was Punjab Province, Pakistan and respondents were selected from six districts selected from three parts of the province that is South, Central and North Punjab of Pakistan on the basis of available and convenience including males and females. Data was collected from (N=519) respondents.Findings: Findings of the study showed positive and significant relationship among the variables. The study accomplished that infotainment programs have enormous effects in providing entertainment among public. Respondents demanded more infotainment programs to reduce their complexities.Originality: Furthermore study concluded that one of three hypothesis that is infotainment programs as source of entertainment supported and two hypothesis that is infotainment programs role in promoting culture and vulgarity not supported.